Student Management at Airmadidi Christian High School - Cicilia Indry Singal; Deitje Adolfien Katuuk; Shelty Deity Meity Sumual (Journal of Social Research, 2023)
The research conducted at Airmadidi Christian High School focused on student management, with specific objectives centered around planning, implementation, and evaluation of these practices. Employing a qualitative approach, the study delved into the intricacies of student management at the institution, situated in Airmadidi Bawah Subdistrict. The research unfolded between June and August 2023, providing a comprehensive examination of the current state of affairs. Upon meticulous examination, it was revealed that the implementation of student management at Airmadidi Christian High School has not reached an optimal level. Despite the concerted efforts by the school and its foundation to enhance the system, certain programs face challenges hindering their full realization. The findings underscore the need for ongoing development and improvement in student management strategies. The research sheds light on the existing gaps and areas for enhancement, serving as a valuable resource for the school and foundation to refine their approaches and ensure the effective management of students in the future. The study contributes valuable insights to the broader field of education management, emphasizing the importance of continuous evaluation and adaptation in fostering an environment conducive to student success.